Trace Amines and the Trace Amine-Associated Receptor 1: Pharmacology, Neurochemistry, and Clinical Implications - Pei, Yue; Asif-Malik, Aman; Canales, Juan J. (Frontiers in Neuroscience, 2016)
Biogenic amines are a collection of endogenous molecules that play pivotal roles as neurotransmitters and hormones. In addition to the “classical” biogenic amines resulting from decarboxylation of aromatic acids, including dopamine (DA), norepinephrine, epinephrine, serotonin (5-HT), and histamine, other biogenic amines, present at much lower concentrations in the central nervous system (CNS), and hence referred to as “trace” amines (TAs), are now recognized to play significant neurophysiological and behavioral functions. At the turn of the century, the discovery of the trace amine-associated receptor 1 (TAAR1), a phylogenetically conserved G protein-coupled receptor that is responsive to both TAs, such as β-phenylethylamine, octopamine, and tyramine, and structurally-related amphetamines, unveiled mechanisms of action for TAs other than interference with aminergic pathways, laying the foundations for deciphering the functional significance of TAs and its mammalian CNS receptor, TAAR1. Although, its molecular interactions and downstream targets have not been fully elucidated, TAAR1 activation triggers accumulation of intracellular cAMP, modulates PKA and PKC signaling and interferes with the β-arrestin2-dependent pathway via G protein-independent mechanisms. TAAR1 is uniquely positioned to exert direct control over DA and 5-HT neuronal firing and release, which has profound implications for understanding the pathophysiology of, and therefore designing more efficacious therapeutic interventions for, a range of neuropsychiatric disorders that involve aminergic dysregulation, including Parkinson's disease, schizophrenia, mood disorders, and addiction. Indeed, the recent development of novel pharmacological tools targeting TAAR1 has uncovered the remarkable potential of TAAR1-based medications as new generation pharmacotherapies in neuropsychiatry. This review summarizes recent developments in the study of TAs and TAAR1, their intricate neurochemistry and pharmacology, and their relevance for neurodegenerative and neuropsychiatric disease.